Informed consent for genetic information management in Colombian law. (2011)
Deciphering the human genome has allowed the development of new health care ways which have been generically referred to as genomic medicine. However, this new knowledge is not devoid of risks related to the access and use of genetic information, involving not only the individual, but also the biological family, ethnic group and community to which he/she belong to. This affects both individual and collective rights, which must be protected by law. This manuscript reviews the Colombian law, specifically in terms of the access and use of genetic information for diagnostic and treatment purposes, focusing on the informed consent process. The concept of genetic information, the risks and benefits associated with genetic data management and the description and critical analysis of the present Colombian regulations were thus reviewed. As a conclusion, the juridical framework of Colombia shows deficiencies regarding the protection of both individual and collective rights linked to the access and use of genetic information.